Selection of suitable fragment from rbcL gene for DNA barcode analysis of family Halymeniaceae, Rhodophyta - Vy, Nguyen Xuan; Thu, Nguyen Nhat Nhu; Hieu, Nguyen Trung; Thuy, Nguyen Thi Xuan (Vietnam Journal of Marine Science and Technology, 2019)
Among the members of Halymeniaceae family, Grateloupia sensu lato occupies the largest composition in species. Classification based on morphological traits is difficult due to the highly variable terete to blade-like thalli among the members of this genus that usually leads to misidentification. Molecular systematics has been applied to classify Grateloupia sensu lato so that the taxonomists acquire a better understanding of the species diversity in general. The plastid gene encoding the large subunit of ribulose-1,5-bisphosphate-carboxylase-oxygenase (rbcL) was the focus of numerous marine algal studies concerning phylogeny and molecular evolution. However, using the full length of rbcL showed disadvantages such as cost and time consuming due to two times of sequencing and two times of PCR. In the present study, the shorter sequence, fragment 773 bp at 5’ end and fragment 579 bp at 3’ end of rbcL were applied and compared for the phylogenetic analysis of Halymeniaceae members. The results indicated there are no differences of topological phylogenetic trees, species resolution within genus and genus resolution within the family between fragment 773 bp at 5’ and the full length of rbcL. Therefore, we conclude that fragment 773 bp at 5’ should be used as DNA barcodes for the Halymeniaceae to reduce the cost and time during phylogenetic analysis. Two taxa Grateloupia newly collected in Vietnam were grouped to the known Phyllymenia, a new genus in Vietnam.